2014
DOI: 10.1039/c4cp01439a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of free-standing, curved Si nanowires through mechanical failure of a catalyst during metal assisted chemical etching

Abstract: The fabrication of orderly arrays of free-standing, curved Si nanowires over large areas (1 cm × 1 cm) was demonstrated by means of interference lithography and intentional mechanical failure of a perforated Au catalyst during metal assisted chemical etching. Photoresist microgrooves were deposited on the perforated Au film to cause uneven etching which resulted in the build-up of bending stresses in the Au film to the point of catastrophic failure. By considering the initial positions of the holes in the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The unbalanced etching can possibly be prevented by the use of isotropic spherical particles, so that the etch rate variations caused by catalyst thickness variation or transport processes are reduced . The importance of geometry in affecting catalyst motion is also shown by Hildreth and co-workers when they found that small or asymmetric catalysts are generally most prone to movement during etching. ,,, Asymmetric catalysts can cause differences in etch rates due to the differences in shapes or exposed edges that can better facilitate the transport of etchant/reactant. The explanation using unbalanced etch rates can also be compared against the model proposed by Sakdinawat and Chang. , The latter reported on the nonuniform distribution of electrons and holes (etch rates) in the deviation of the isolate catalyst, which is reduced when larger catalyst strips are placed near the isolate catalysts to reduce the carriers splaying effect. , Finally, we believe that the unbalanced etch rate explanation is also consistent with the suggestion that the perturbation from hydrogen gas produced during etching is the cause for catalyst motion .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The unbalanced etching can possibly be prevented by the use of isotropic spherical particles, so that the etch rate variations caused by catalyst thickness variation or transport processes are reduced . The importance of geometry in affecting catalyst motion is also shown by Hildreth and co-workers when they found that small or asymmetric catalysts are generally most prone to movement during etching. ,,, Asymmetric catalysts can cause differences in etch rates due to the differences in shapes or exposed edges that can better facilitate the transport of etchant/reactant. The explanation using unbalanced etch rates can also be compared against the model proposed by Sakdinawat and Chang. , The latter reported on the nonuniform distribution of electrons and holes (etch rates) in the deviation of the isolate catalyst, which is reduced when larger catalyst strips are placed near the isolate catalysts to reduce the carriers splaying effect. , Finally, we believe that the unbalanced etch rate explanation is also consistent with the suggestion that the perturbation from hydrogen gas produced during etching is the cause for catalyst motion .…”
Section: Introductionmentioning
confidence: 98%
“…29 The importance of geometry in affecting catalyst motion is also shown by Hildreth and co-workers when they found that small or asymmetric catalysts are generally most prone to movement during etching. 16,18,23,31 Asymmetric catalysts can cause differences in etch rates due to the differences in shapes or exposed edges that can better facilitate the transport of etchant/reactant. The explanation using unbalanced etch rates can also be compared against the model proposed by Sakdinawat and Chang.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for the fabrication of Si nanogratings in this study is similar to that previously reported for the synthesis of nanostructures on silicon (Si) and polymeric substrates. Briefly, P-type (100) Si wafers were first cleaned with acetone and dipped in hydrofluoric acid (HF) for 60 s to remove the native oxide. Four hundred nanometers of Ultra-i-123 positive photoresist was then spin coated onto the surface and baked at 110 °C for 90 s. The wafers were diced into 1 cm × 1 cm samples and exposed to interference lithography using a He–Cd laser with a wavelength of 365 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Under these conditions, the etching follows non-<100> directions (Figures S1 and S2 ). It was reported that at high ε, the amount of generated holes increases and can polarize more Si back-bonds resulting in non-<100> etching 31 , 36 . To generate the high aspect ratio k-SiNWs, the etching was quenched every 5 minutes by immersing the Si substrate in methanol.…”
Section: Continuous Synthesis Of K-sinws Sustained By Chemical Peelinmentioning
confidence: 99%